2022
DOI: 10.1037/cou0000599
|View full text |Cite
|
Sign up to set email alerts
|

The “dyadic dance”: Exploring therapist–client dynamics and client symptom change using actor–partner interdependence modeling and multilevel mixture modeling.

Abstract: Using longitudinal actor-partner interdependence modeling and multilevel mixture modeling, the aims of this study were to investigate the therapist-client dyadic dynamic patterns (i.e., therapist and client consistency and their mutual influences in perceptions of working alliance) and how these dynamic patterns related to client symptom change with varied treatment lengths. Data set included 1,520 sessions conducted by 85 master's level therapist trainees with their 283 clients in China. Before every session,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…For the client, learning to empathize with others (Chui et al, 2021; MacFarlane et al, 2017; Yalom, 2002), in this case to the therapist’s emotional experience, may be an important part of the psychotherapy process and also interpersonal learning and growth. A recent study also showed that mutual influence between therapist and client is associated with positive client outcome (Li, 2021). In short, the effect of AA on client-rated therapist empathy and session quality may be attributed to both members of the dyad.…”
Section: Discussionmentioning
confidence: 99%
“…For the client, learning to empathize with others (Chui et al, 2021; MacFarlane et al, 2017; Yalom, 2002), in this case to the therapist’s emotional experience, may be an important part of the psychotherapy process and also interpersonal learning and growth. A recent study also showed that mutual influence between therapist and client is associated with positive client outcome (Li, 2021). In short, the effect of AA on client-rated therapist empathy and session quality may be attributed to both members of the dyad.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a host of studies have suggested that both the therapist’s and the client’s WA perceptions could predict session outcomes and client outcomes either individually (e.g., Kivlighan et al, 2014; Zilcha-Mano et al, 2018) or jointly through their synchrony/congruence (e.g., Marmarosh & Kivlighan, 2012; Zilcha-Mano, 2017) or shared component (Li et al, 2021). In addition, using a dynamic modeling approach, Li (2022) revealed that a dynamic pattern characterized by the therapist and client maintaining some consistency of their own perceptions of WA but also having mutual influences on each other’s WA perceptions was associated with more positive client symptom improvement. These findings lend support to the need for the therapist to track and be attuned to the client’s WA perceptions by being open, curious, and perceptive in the session, but perhaps also through an instated tracking system of therapists’ and clients’ treatment process, and outcome variables (such as WA).…”
Section: Measuring Working Alliance Longitudinally: Current Status An...mentioning
confidence: 99%